2010
DOI: 10.1007/s00330-010-1914-4
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion-weighted imaging perfusion fraction f is a potential marker of sorafenib treatment in advanced hepatocellular carcinoma: a pilot study

Abstract: Contrary to ADC and D, the perfusion fraction f is a valuable marker of sorafenib treatment in advanced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
132
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 33 publications
(48 reference statements)
10
132
1
Order By: Relevance
“…However, they reflect different aspects of perfusion: D* is related to the length and velocity of the capillary network, whereas f reflects the fraction of the microcirculation that accounts for all diffusion in voxels. Unsurprisingly, several studies have observed similar mismatches for D* and f (29,(31)(32)(33), even in dynamic contrast enhancement research (34), which is another type of perfusion-related hemodynamic model. One convincing explanation for this contradiction is that f is dependent on echo time (TE): the longer the TE, the larger the f value.…”
Section: Discussionmentioning
confidence: 89%
“…However, they reflect different aspects of perfusion: D* is related to the length and velocity of the capillary network, whereas f reflects the fraction of the microcirculation that accounts for all diffusion in voxels. Unsurprisingly, several studies have observed similar mismatches for D* and f (29,(31)(32)(33), even in dynamic contrast enhancement research (34), which is another type of perfusion-related hemodynamic model. One convincing explanation for this contradiction is that f is dependent on echo time (TE): the longer the TE, the larger the f value.…”
Section: Discussionmentioning
confidence: 89%
“…For example, the perfusion parameter can be used as a biomarker for predicting the responsiveness of some types of tumors to chemotherapy. 11,12 Therefore, estimating these 2 distinctive phenomena in tumor tissues may be helpful in the preoperative characterization of tumors. A simplified IVIM MR imaging technique based on the IVIM model was used to assess the PP and D of hepatocellular carcinomas.…”
Section: Resultsmentioning
confidence: 99%
“…A simplified IVIM MR imaging technique based on the IVIM model was used to assess the PP and D of hepatocellular carcinomas. 12 In that study, the PP was determined with 4 b-values (0, 200, 400, and 800 s/mm 2 ), a technique that is easy to apply and fast compared with the IVIM imaging by using multiple b-values (eg, 0, 10, 20, 30, 50, 80, 100, 200, 400, and 800 s/mm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, literature data are controversial. Lewin et al [107] reported a significant f (perfusion fraction) increase in responders at 2 wk and at 2 mo of sorafenib therapy, whereas a decrease was noted in non-responders at the same time intervals. Vouche et al [108] reported that ADC values did not change 1 and 3 mo after 90 Y TARE or 90 Y TARE plus sorafenib treatments.…”
Section: Primary Liver Tumorsmentioning
confidence: 98%
“…Sunitinib seems to induce K trans and Kep decrease and ADC increase [113,114] ; these modifications can be assessed even at a very early stage (after 2 wk of treatment). Lewin et al [107] 12 IVIM f increase HCC sorafenib Vouche et al [108] 15 DWI ADC increase HCC 90 Y TARE ± sorafenib…”
Section: Primary Liver Tumorsmentioning
confidence: 99%